LABOUR EXPLOITATION, SYSTEMATIC OPPRESSION AND VIOLENCE IN PALM OIL PLANTATIONS IN NORTH SUMATRA, INDONESIA - Heupner, Susan Groot (PEOPLE: International Journal of Social Sciences, 2016)
Although it has been almost two decades since the fall of the Suharto regime, political reform and democratization has not sufficiently challenged realities of systematic oppression, coercion and violence experienced by workers in palm oil plantations in North Sumatra, Indonesia. The research aims to expose the various ways in which the independent trade union is forced to manoeuvre within and against this system in its attempt to empower workers and built a strong political force. Although the tribune in Indonesia is built on legally binding pillars, these are proven too weak and corrupt for trade unionists to organize and emancipate plantation workers. This can partly be attributed to a history of ideological suppression and decades of authoritarian rule, and partly to the demands of modern capitalism and global production chains in need for what Laura Ann Stolers refers to as a cheap, socially malleable and politically inarticulate labor force. Based on several months of first-hand observation of, and participation in, trade union activity, the study reveals the deeply embedded power structures that sustain all the elements of the plantation system. Moreover, the analysis shows how the squeeze of labor and capital resembles a system of slavery that has dissolved centuries ago. As a conclusion, the paper argues the plantation is a system of violence that facilitates the ‘slavish submission’ of plantation workers and works in manipulative ways to tear down the pillars of the tribune from which trade unionists attempt to speak.